High risk pregnancy with sacrococcygeal teratoma - Sharma, Snigdha; Sharma, Arti; Maletha, Madhukar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Sacrococcygeal teratoma (SCT) is the most common tumor of the newborn period. Most cases are diagnosed prenatally during ultrasound imaging. If fetal hydrops develops, urgent intervention is done to minimize fetal morbidity (or mortality). Management depends on fetal lung maturity and tumor size. Most cases are benign and require only minimal intervention. Once fetal maturity is achieved at 37 weeks, scheduled delivery is planned. Complete resection of tumor including coccyx is vital to prevent malignant recurrence. Strict follow up and AFP monitoring is important. Small percentage become malignant and can occur even after tumor removal.